2022
DOI: 10.3389/fneur.2022.856919
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Brain Changes After Stroke and the Association With Cognitive Decline

Abstract: BackgroundCognitive impairment is common after stroke. So is cortical- and subcortical atrophy, with studies reporting more atrophy in the ipsilesional hemisphere than the contralesional hemisphere. The current study aimed to investigate the longitudinal associations between (I) lateralization of brain atrophy and stroke hemisphere, and (II) cognitive impairment and brain atrophy after stroke. We expected to find that (I) cortical thickness and hippocampal-, thalamic-, and caudate nucleus volumes declined more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…In terms of SBM analysis, poststroke patients exhibited decreased CT in the contralesional PreCG, lingual and fusiform gyrus, and IPL, in accordance with several previous studies (Aamodt et al, 2022; Salah Khlif et al, 2022), mirroring the atrophy of the contralesional hemisphere. There are several factors that can account for the thinning of the contralesional cortex, including ‘transcallosal diaschisis’, apoptosis induced by ipsilesional interneurons, Wallerian or retrograde degeneration of fibre tracts, and ‘non‐use cortical atrophy’ (Carrera & Tononi, 2014; Cheng et al, 2020; Kraemer et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…In terms of SBM analysis, poststroke patients exhibited decreased CT in the contralesional PreCG, lingual and fusiform gyrus, and IPL, in accordance with several previous studies (Aamodt et al, 2022; Salah Khlif et al, 2022), mirroring the atrophy of the contralesional hemisphere. There are several factors that can account for the thinning of the contralesional cortex, including ‘transcallosal diaschisis’, apoptosis induced by ipsilesional interneurons, Wallerian or retrograde degeneration of fibre tracts, and ‘non‐use cortical atrophy’ (Carrera & Tononi, 2014; Cheng et al, 2020; Kraemer et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Significances are indicated by asterisks. For sensitivity analyses, surviving correlative outcome models were re-computed while iteratively taking various potentially confounding factors into account: (i) side of the lesion including its interaction with the regional volume to account for hemispheric specialization of basal ganglia 48-50 and possible lateralization effects 51 and differential plasticity rates 52 known from traumatic brain injury patients; (ii) peak width of skeletonized mean diffusivity (PSMD) of the unaffected hemisphere as a marker of cerebral small vessel disease burden 53 ; and (iii) influence of initial symptom severity onto volumetry–outcome relationship as operationalized by the interaction between NIHSS (dichotomized by median split into higher and lower NIHSS scores) and regional volume. For specificity analyses, we computed additional outcome models which included only global—and not regional—parameters of structural reserve that are (i) TIV; (ii) averaged grey subcortical matter volume; and (iii) averaged cortical grey matter volume of the unaffected hemisphere.…”
Section: Methodsmentioning
confidence: 99%
“… 40 Longitudinal tracking is therefore required to record potential pathological changes following stroke. 41 PET imaging is a strong tool in both research and clinical use because it has been used for metabolic-biochemical-molecular studies in vivo and in a minimally invasive manner. 42 , 43 Studies using 18F-FDG in both preclinical and clinical settings have consistently reported that 18F-FDG absorption is lower in areas thought to be the site of ischemic injury.…”
Section: Discussionmentioning
confidence: 99%